CASE OF PROGRESSING ALVEOCOCCOSIS - Талицкая, Елена Анатольевна; Близнюк, Алексей Анатольевич; Саблина, Ольга Константиновна; Калитина, Светлана Владимировна (Medicine in Kuzbass, 2019)
Alveococcus (alveolar echinococcosis, multichamber echinococcosis) is helminthiasis from the group of cestodosis. Alveococcus has some syndromes, such as heavy chronic process, primary tumor of the liver for which is characteristic infiltrative parasitic tissue growth, sometimes with metastases to the brain and lungs as well as to other organs. This disease is always lethal. The probability of survival after 10 years is only 10-20 % without therapy. The surgery with removal of the parasitic tumor is method of patient choice and the only radical solution for the treatment. A chemotherapy with antihelmintic drugs is efficient only in some cases. Goal: is to present clinical case of progressing alveococcus, what was caused by the long-term active immunosuppressive therapy after liver transplantation. This one leads to growth of parasites and the ineffectiveness of antiparasitic treatment with albendazole. Results. In the article the case of spread alveolar liver echinococcosis Р4, Nx, Mx is described, the state is after liver transplantation (1994). The condition is after a lot of surgeries of removal of metastatic parasitic nodes in the retroperitoneal space, spine, anterior thoracic and abdominal wall (1996-2009), complicated by multiple metastases of alveococcus in the lungs, brain, gates of the liver and retroperitoneal space, deep vein thrombosis of the lower extremities. Application. Gastroenterology.